Holistic thoughtful classroom for promoting higher order thinking skills in the 21st Century Learning - Embong, Rahimah; Wan Yusoff, Wan Mazwati; Che Seman, Shamilati; Hashim, Huda Afiqah; Md Lateh @ Junid, Hanif (IATED, 2022)
The Fourth Industrial Revolution (IR4.0) brings technology into our everyday lives, making education accessible anytime, anywhere. To align with the fourth industrial revolution is challenging for any education system especially when content and structure of school curriculum do not change as fast as changes in technological advancement. Therefore, the only logical step to do is to prepare students as independent learners by providing them with essential skills of 21st-century learning, one of which is higher order thinking skill (HOTS). However, the implementation of HOTS in teaching and learning (TnL) seems to be problematic at schooling level. This is associated with the lack of knowledge and experiences among teachers to infuse effectively thinking skills in their classrooms. The success of developing HOTS in students depended highly on teachers’ knowledge and skills in HOTS. The first step in training teachers to have knowledge and competence in HOTS is to present clear theoretical framework of what constitute excellent thinking behaviour. This paper elucidates three dimensions of teaching thinking namely habits of mind posited by Costa (2001), human passion by Costa and Garmston (2001) and language of thinking by Costa and Marzano (1991). The review revealed entwined and overlapping elements which were synthesized to come up with a more holistic framework of thinking behaviour. It consists of six components which are creative thinking, flexible thinking, interdependence thinking, metacognition, precision in thinking and self-efficacy. This framework is suggested to be the foundation for developing an educational model of Holistic Thoughtful Classroom as a guide for teachers to implement effectively HOTS in their classrooms. This paper suggests some implications on effective thoughtful teachers, conducive classroom learning as well as uniqueness, learning styles and readiness to think among students at all levels of schooling in general.